Splitting in-patient and out-patient responsibility does not improve patient care. (January 2017) - Burns, Tom; Baggaley, Martin
Summary: Over the past 15 years there has been a move away from consultants having responsibility for the care of patients both in the community and when in hospital towards a functional split in responsibility. In this article Tom Burns and Martin Baggaley debate the merits or otherwise of the split, identifying leadership, expertise and continuity of care as key issues; both recognise that this move is not evidence based.